Edge Computing Networks by Using Wsns with Efficient Distributed Leader Election for Measuring Air Pollution - Miranda-Sandoval, M; Fernandez-Campusano, C (Springer Science and Business Media Deutschland GmbH, 2025)
Monitoring environmental conditions is of paramount importance for identifying and mitigating pollution sources. Air quality is a crucial factor, and sensors monitor pollutants such as PM2.5, PM10, NO2, and O3. Ubiquitous systems have the ability to monitor these measurements. One of the biggest challenges for networks in ubiquitous systems is reliability, which requires Distributed Leader Election (DLE) algorithms. The elected leader ensures data reliability from the network layer to Edge Computing (EC), improving latency between Wireless Sensor Network (WSN) and Cloud Computing (CC). This paper proposes a three-layer architecture: Internet of Things (IoT), Edge Computing (EC) with Field-Programmable Gate Array (FPGA), and Cloud Computing (CC). Our findings show that the architecture improves monitoring, leader selection, and air quality data accuracy, thus optimizing system reliability. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.